The PLATO Mission. Issue 8 (30th September 2016) - Rauer, H.; Aerts, C.; Cabrera, J.; PLATO Team
Abstract: We present the current status of the PLATO space mission, which is currently in its design phase. A brief overview of its capabilities is given, after introducing the core science goals of the mission. We also present the amount of observing time offered to the community as Guest Observer program. This will allow a wealth of complementary science in many areas of astro‐physics, ranging from stellar to extragalactic science and covering variability phenomena with time scales from a few seconds to years.